The Blame Game: Narratives of Electoral Defeat and Party Change. The Case of Four Polish Political Parties - Bachryj-Krzywaźnia, Maciej (Historia i Polityka, 2021)
The purpose of the article is to present party elites’ narratives about electoral defeat in order to identify characteristics of the narratives which may inhibit or facilitate party change. The opening sections explain theoretical approach and methodology adopted for the research. The next paragraphs reconstruct and compare narratives of four Polish political parties, which experienced electoral defeat in 2011 and 2015 parliamentary elections, and give a psychological explanation for their emergence. As a result, four narrative strategies were identified of which only one seems to have potential to facilitate party change. Its distinctive feature is internalization of blame, whereas the others reveal tendency to denial or personalize and externalize blame.